Errors and Exceptions in Endodontic Exercises - Kholboeva Nasiba Asrorovna; Abdusattorova Gulbakhor Nazarovna; Mamatov Hamid Boymurod ugli; Asatbayev Jaloliddin Asliddin ugli (Genius Journals, 2023)
The article discussed in details the factors affecting the success or failure of endodontic treatment, the protocol of root canal irrigation is given, endodontic treatment errors are analyzed.
Keywords: root canal; complications of endodontic treatment